Acceleration of wound healing potential by lantana camara leaf extract in experimental rats - Abdulla, M.A.; Khalil, W.I.; Rokik, R.H.; Bashah, N.S.A.; Mahmoud, F.H.; Noor, S.M.; Ali, Hapipah Mohd; Hassandarvish, P. (2009)
The ethanolic extract of Lantana camara leaf was evaluated for their wound healing potential in rats. Four grouhs of adult male Wistar albino rats were experimentally wound in the posterior neck area. A thin layer of blank placebo Was applied topically to wounds of Group 1. Wound of Group 2 and 3 animals were dressed with a thin layer of placebo containing 5 and 10% L. canzara extract, respectively. A thin layer of intrasite gel was applied topically to wounds of Group 4 animals as reference. The effects of these topical applicants on the rate of wound healing mid histology were assessed. Wound dressed with placebo containing plant extracts significantly healed earlier than those treated with blank placebo. Wounds dressed with placebo containing 10% extract significantly accelerate wound healing activity compared to wounds dressed with placebo containing 5% extract. Histological analyses of healed wounds confirmed the results. Wounds dressed with placebo containing extracts showed markedly less sear width at the wound enclosure and wounds contained large amounts of fibroblast proliferation and more mature and densely packed collagen with accompanying angiogenesis compared to wounds dressed only with blank placebo. We conclude that L. camara extract significantly enhanced the acceleration rate of wound enclosure in rats. © Medwell Journals, 2009.